On crystallization of law - Szmodis Jenő (Anali Pravnog Fakulteta u Beogradu)
The article introduces the problem of autonomy of law. The paper examines the medieval origins of legal positivism from a historical approach, sketching the main theories concerning the emergence of law, and phrasing some preliminary consideration for a historical and philosophical view of the problem of the birth of law. As a result of reasoning the article suggests some legal historical and human ethological ideas relating to the phenomena of crystallization of the law.